RIDING HERD ON ACCOUNTING STANDARDS. - Bevis, Herman W. (The Accounting Review, 1961)
Abstract In this article author examines questions of accounting standards. In examining the question of accounting standards, uniform or otherwise, it is necessary to consider the fundamental nature and purpose of accounting. Author starts with the broad definition of accounting as the measurement and communication of financial and other economic data. Its end product is information. The end purpose of this information is to assist someone in formulating judgments and making decisions. Communications of economic data generated in any one organization may be for internal, or for external, purposes. Standards used in the measurement and communication of data must be practicable for the issuer and useful to the user. They must be practicable in that, providing always that the accountability requirements of stewardship are met, they must be capable of being applied without undue effort and delay by the issuer in originating the data. Some accounting standards might preferably differ, for example, between the electric utility serving a huge metropolitan area, and the new electronic company whose whole future depends on its research.